A Fish of Multiple Faces, Which Show Us Enigmatic and Incredible Phenomena in Nature: Biology and Cytogenetics of the Genus Carassius - Knytl, Martin; Forsythe, Adrian; Kalous, Lukáš (International journal of molecular sciences, 2022)
Sexual vs. asexual reproduction-unisexual vs. bisexual populations-diploid vs. polyploid biotypes-genetic vs. environmental sex determination: all these natural phenomena are associated with the genus of teleost fish, Carassius. This review places emphasis on two Carassius entities with completely different biological characteristics: one globally widespread and invasive Carassius gibelio, and the other C. carassius with a decreasing trend of natural occurrence. Comprehensive biological and cytogenetic knowledge of both entities, including the physical interactions between them, can help to balance the advantages of highly invasive and disadvantages of threatened species. For example, the benefits of a wide-ranged colonization can lead to the extinction of native species or be compensated by parasitic enemies and lead to equilibrium. This review emphasizes the comprehensive biology and cytogenetic knowledge and the importance of the Carassius genus as one of the most useful experimental vertebrate models for evolutionary biology and genetics. Secondly, the review points out that effective molecular cytogenetics should be used for the identification of various species, ploidy levels, and hybrids. The proposed investigation of these hallmark characteristics in Carassius may be applied in conservation efforts to sustain threatened populations in their native ranges. Furthermore, the review focuses on the consequences of the co-occurrence of native and non-native species and outlines future perspectives of Carassius research.
Keywords: Animals; Ploidies; species; cytogenetické vyšetření; Cyprinidae; diploidie; Cytogenetic Analysis; ploidie; cytogenetika; biotype; ploidy level; hybridization; sex determination; Diploidy; Cytogenetics; zvířata; Carassius auratus complex; sexuality; asexuality